Kepribadian Dan Ikigai Tokoh Utama Pelaku Pembunuhan Dalam Film Kokuhaku - Pungkasari, Diani Ratna; Lusiana, Yusida; Kadafi, Muammar (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 3 No 2 (2021), 2021)
This study aims to examine the relation between the character's personality and the Japanese motivational concept of ikigai on the murderers of the Kokuhaku’s movie, Yuko Moriguchi, Shuya Watanabe, and Naoki Shimomura. The method used in this study is a qualitative descriptive method with a literary psychology approach. The data analysis technique used is the listening technique followed by the note-taking technique. The personality theory used is Carl G. Jung's theory of personality typology, and the concept of ikigai in this study uses the concept by Akihiro Hasegawa. The results of this study indicate that Yuko Moriguchi has an extroverted-thinking personality and her ikigai is her daughter, then Shuya Watanabe has an introverted-thinking personality with gaining recognition as his ikigai, and Naoki Shimomura has an introverted-thinking personality and his ikigai is gaining recognition. The conclusion that can be drawn from this research is that a person's personality and ikigai influence each other, especially in their behavior.